Identifying causes and remedies for cost overruns in Botswana's public construction projects - Dibonwa, Pelontle (My University, 2009)
This research survey was carried out to investigate three areas of concern which are commonly associated with the implementation of government development projects: namely: (i) cost overrun causal factors, (ii) effective remedial cost control measures and (iii) apportionment of professional responsibility for either cost overrun causal factors or costs control remedial measures’ implementation. The ultimate aim was to identify major causes of cost overruns, generate and recommend possible solutions to the problem of cost overruns in the Botswana public construction industry. The research strategy adopted, involved the circulation of questionnaires and subsequent statistical data analysis. Initially, an expert group questionnaire test survey was conducted among ten (10) professionals (expert group), in order to solicit professional opinion and contributory input on the research. The purpose of the expert group questionnaire test survey was to refine the research questionnaires, make necessary questionnaire structure amendments, eliminate possible ambiguities, and finally, to make data collection an easy exercise. Through the expert group questionnaire test survey, the research questionnaires were assessed for validity and reliability. Thus, the questionnaire content validity (Saunders et al. 2003) was established by soliciting comments from the expert group, on the representativeness and suitability of the research questionnaires. Lists of causes of cost overruns factors and effective cost control measures were, developed for each of the three major project development cycle phases; namely: the conception/planning/designing, implementation, and completion/commissioning phases. The research questionnaires which were formulated through expert group questionnaire test survey lists of cost overruns causal factors and cost control remedial measures were circulated to a wide range of practicing professionals. In addition, a representative number of case study projects, with specific reference to cost overruns and cost control, were selected for detailed investigation. Three statistical data analytical methods; the respondents ‘s cost overrun factor/cost control measures ranking order, the Kendell’s Correlation Coefficient and the case study analysis, were simultaneously (triangulation analysis), employed in order to draw conclusive results of the research findings. Hence, the result of the survey identified: i) the most frequent cost overrun causal factors; as inadequate project brief, insufficient/inadequate project design, lack of project coordination and contractual claims and ii) the most effective cost control measures; as appointment of competent project personnel, improved project monitoring, awarding contracts to reputable/competent contractors and monitoring teams and providing time and financial management facilities. The third objective, which was to identify and apportion professional personnel responsibility for causal factors and remedial cost control implementation measures; within each of the three-project development cycle phases; yielded the following results: Clients and project managers were found to play a major contributory role in activities that lead to project cost overruns at conception/planning/designing phase. The project implementation phase allocated blame to contractors, architects and quantity surveyors for cost overruns, while quantity surveyors and contractors were found to be responsible for cost overruns at the completion/commissioning phase. On the implementation of effective remedial cost control measures, the professional responsibility scenario was found to be as follows: clients and project managers play a major role at conception/planning/designing phase, whereas quantity surveyors are key players at implementation phase and project managers; at completion /commissioning phase.
Keywords: Cost overruns; Causal factors; Cost control